The Quality of the New Generator Sequence Improvent to Spread the Color System’s Image Transmission - Mohamed Krim; Adda Ali Pacha; Naima Hadj Said (Universitas Ahmad Dahlan, 2018)
This paper shows a new technic applicable for the digital devices that are the result of the finite’s effect precision in the chaotic dynamics used in the coupled technic and the chaotic map’s perturbation technics used for the generation of a Pseudo-Random Number Generator (PRNGs).The use of the pseudo- chaotic sequences coupled to the orbit perturbation method in the chaotic logistic map and the NewPiece-Wise Linear Chaotic Map (NPWLCM). The pseudo random number generator’s originality proposed from the perturbation of the chaotic recurrence. Furthermore the outputs of the binary sequences with NPWLCM are reconstructed conventionally with the Bernoulli’s sequences shifts map to change the shapes with the bitwise permetation then the results in simulation are shown in progress.After being perturbed, the chaotic system can generate the chaotic binary sequences in uniform distribution and the statistical properties invulnerable analysis. This generator also has many advantages in the possible useful applications of spread spectrum digitalimages, such as sensitive secret keys, random uniform distribution of pixels in Crypto system in secure and synchronize communication.